2012
DOI: 10.2220/biomedres.33.175
|View full text |Cite
|
Sign up to set email alerts
|

Intraplantar injection of linalool reduces paclitaxel-induced acute pain in mice

Abstract: Linalool is the principal component of many essential oils known to possess biological activities. We previously reported that intraplantar injection of linalool reduces the nociceptive response as assayed by the capsaicin test. In this study, we sought to determine whether intraplantar injection of linalool could influence the induction of acute pain (allodynia and hyperalgesia) by paclitaxel in mice. Paclitaxel is widely used in cancer chemotherapy for the treatment of solid tumors, but it sometimes induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…), in a volume of 10 μl/g body mass, once per day for 5 consecutive days. Other groups and ours have observed that this treatment regimen produce thermal hyperalgesia in mice 20 21 22 23 24 .…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…), in a volume of 10 μl/g body mass, once per day for 5 consecutive days. Other groups and ours have observed that this treatment regimen produce thermal hyperalgesia in mice 20 21 22 23 24 .…”
Section: Methodssupporting
confidence: 56%
“…The paclitaxel treatment regimen and dose used in this study has been reported to produce painful neuropathy in mice, which manifested as thermal hyperalgesia, cold allodynia and mechanical allodynia 21 22 23 . Our group also previously observed thermal hyperalgesia using the same paclitaxel treatment regimen 20 24 .…”
Section: Discussionmentioning
confidence: 99%
“…the acute pain models (11,23), suggesting that BEO and linalool may be effective in reducing nociception linked to a range of paradigms. The present data suggest that plantar subcutaneous injection of BEO or linalool significantly reduces formalin-induced nociception.…”
Section: Fig 2 Effects Of Bergamot Essential Oil (Beo) (mentioning
confidence: 99%
“…BEO and linalool were diluted in jojoba wax (Simmondsia chinensis) (K.S.A. International Co. Ltd., Kanagawa, Japan) to reach total amounts of 1.25-10 μg (11,23). Jojoba wax alone had no effect on formalin-induced nociception.…”
mentioning
confidence: 99%
“…Linalool has also reported to be protective against ultraviolet B (UVB)-induced tumor through inhibition of inflammation and angiogenesis signaling, as well as induction of apoptosis in the mouse skin [118]. Finally, a study showed that linalool reduced paclitaxel-induced acute pain in mice, which was antagonized by the direct injection of naloxone hydrochloride, suggesting opioid signaling modulation [119]. What can be appreciated so far, and will continue to be addressed, is the general ability of different terpenes to modulate inflammation and oxidative stress through different pathways, which in turn could be very useful to shed light to novel treatments for pain, cancer, autoimmune diseases, and CNS diseases that rely greatly on the impact of these processes.…”
Section: Linaloolmentioning
confidence: 99%